Propensity Score Adjusted Comparison of Minimally Invasive versus Open Thymectomy in the Management of Early Stage Thymoma - Fadayomi, Ayotunde B.; Iniguez, Carlos E. Bravo; Chowdhury, Ritam; Coppolino, Antonio; Jacobson, Francine; Jaklitsch, Michael; Mody, Gita N. (The Thoracic and Cardiovascular Surgeon, 2018)
Background The benefits of minimally invasive versus open thymectomy for the management of thymoma are debatable. Further, patient factors contributing to the selection of operative technique are not well elucidated. We aim to identify the association between baseline patient characteristics with choice of surgical approach.Methods Medical records of early stage thymoma (stages I and II) patients undergoing thymectomy between 2005 and 2015 at a single center were identified. Baseline characteristics and surgical outcomes such as prolonged length of stay (LOS ≥ 4 days), 90-day postoperative morbidity, completeness of resection, and recurrence or mortality free rates were compared by surgical approach.Results Fifty-three patients underwent thymectomy (34 open [64.15%] vs. 19 minimally invasive [35.85%]). There were no statistical differences between the two surgical approaches in demographic variables, smoking status, lung function, comorbidity, tumor size, or staging. Open thymectomy had significantly prolonged LOS (≥4 days) compared with minimally invasive procedures (odds ratio: 11.65; p < 0.01). There were no significant differences in postoperative composite morbidity (p = 0.56), positive margin (p = 0.40), tumor within 0.1 cm of resection margin (p = 0.38), and survival probability estimates (log rank test; p = 0.48) between the two groups.Conclusion Baseline patient characteristics were not associated with surgical approach selected for thymectomy. Minimally invasive thymectomy patients had shorter LOS but no significant differences in 90-day composite morbidity and recurrence or mortality. Larger multicenter studies are needed to evaluate factors contributing to patient selection for each approach, which may include surgeon preference.
Keywords: minimally invasive thymectomy; open thymectomy; thymoma